Assessing Associational Groups’ Participation at Local Level Planning: A Study of Dhulikhel Municipality - Sapkota, Naniram (Multi-Disciplinary Explorations: The Kasthamandap College Journal, 2024)
This study assessed the practice of associational groups’ participation at the local level planning. The purpose of the study was to conceptualize the various means of participation and assess the level of participation in social development and tourism development plans under the Integrated Urban Development Planning (IUDP) of Dhulikhel Municipality. 60 participants were taken using convenience sampling, and the interview was carried out to collect data using semi-structured questionnaire. Descriptive statistics were used to analyze the data. The study shows that various means of participation were used during IUDP formulation. The various means of participation were identified as workshops, surveys, ward meetings, focus group discussion, involving committee and other means respectively in the descending order in terms of involvement of participants. Similarly, the level of participation was found to be placation and partnership in access and control aspects respectively. There was not enough access for participants to participate in IUDP formulation. Therefore, the invitation methods and means of participation should be reviewed so that participation could be enhanced by number, variety, and quality. The study reveals that citizens are allowed to negotiate with those in authority, but final decisions are made with or without regarding citizens’ voices. Those who get access, play decisive roles in controlling plan formulation to some extent. Finally, it can be concluded that increased access to associational groups contributes to controlling the planning by improving their ownership.